(NiSPANSKO(B-(NRUSSKIJ(B, (NRUSSKO(B-(NISPANSKIJ TERMINOLOGI^ESKIJ SLOWARX(B: (NBANKI(B, (NBIRVI(B, (NFINANSY (B:s (NoK(B. 6000 (NTERMINOW (B/s - (NeRMOLENKO(B, (NaLLA wIKTOROWNAs; (NkAWKIN(B, (NaLEKSANDR wALERXEWI^s ((NmOSKWA (B:s (NtEZAURUS(B,s, 2004)
(Nw SLOWARE NA[LI OTRAVENIE TERMINY(B, (NISPOLXZUEMYE W SOWREMENNOJ SPECIALXNOJ ISPANO(B-(NQZY^NOJ NAU^NOJ LITERATURE I PERIODI^ESKIH IZDANIQH(B, (N^TO OBUSLOWLIWAET EGO AKTUALXNOSTX(B. (NdLQ SPECIALISTOW(B, (NWLADE@]IH ISPANSKIM QZYKOM(B, (NPEREWOD^IKOW(B, (NPREPODAWATELEJ(B.s
Keywords: (N|KONOMIKAs; (NmIROWAQ \KONOMIKAs; (NfINANSY (B- (NtERMINOLOGI^ESKIJ SLOWARXs